(untitled) (American Journal of Islam and Society, 2015)
The polyvalent Qur’anic text lends itself to multiple interpretations, depending upon one’s presuppositions and premises. In fact, Q. 3:7 distinguishes between muḥkam (explicit, categorical) and mutashābih (metaphorical, allegorical, symbolic) verses. As such, this device provides a way for reinterpreting verses that outwardly appear to be problematic – be it in the area of gender equality, minority rights, religious freedom, or war. However, many of the verses dealing with legal provisions in such areas as devotional matters, marriage, divorce, child custody, inheritance and bequest, and specific punishments appear to be unequivocal, categorical, and explicit. As such, scholars have devised certain hermeneutical strategies to situate and contextualize these verses in a particular socio-historical context, as well as to emphasize that they were in conversation with the society to which the Qur’an was revealed and thereby underlining the “performative” (p.15) nature of the relationship between the Qur’an and the society. No verse is more problematic, in the sense that it offends contemporary sensibilities and is quite difficult to reconcile with an egalitarian worldview when dealing with gender issues, than Q. 4:34, which allows the husband to discipline his wife if he deems her guilty of nushūz (e.g., disobedience, intransigence, sexual lewdness, aloofness, dislike or hatred of himself). Ayesha Chaudhry undertakes a study of this challenging verse by engaging the corpus of literature in Arabic from the classical period to the seventeenth century; she also includes Urdu and English sources for the post-colonial period. She starts off by relating her personal journey from a state of discomfort and puzzlement when she first came across this verse in middle school to a defensive posture in trying to convince herself by invoking the Prophet’s compassion toward his wives and in cherishing the idea that the Qur’an gave more rights to women than either the Hebrew Bible or the New Testament. She began a more rigorous and nuanced study of this verse after equipping herself with the necessary academic tools and analytic skills during her university studies. Frustrated with the shallow responses and the scholars’ circumspection as regards any creative and novel reading of the verse for fear of losing their status in the community, she decided to do so herself with the hope of discovering views that would promote an egalitarian reading. But ...